Challenges and Learning Strategy for young children with special needs during the pandemic in Indonesia - Fridani, L.; Ikegami, Kiiko (Anthology Challenges in Management of Early Childhood Education during Pandemic, 2021)

Enhancing Teacher Education by Utilizing a Revised PGDE Curriculum as a Fundamental Resource for Inclusive Practices in Macao - Monteiro, Elisa; Forlin, Chris (International Perspectives on Inclusive Education, 2021)
Keywords: Inclusive education; Knowledge transfer; Pedagogical practice; Post-graduate diploma in education; Programme design; Teachers

Forming Intercultural Missionaries - Gallares, Judette (Becoming Intercultural: Perspectives on Mission, 2021)

Liturgical Text as Mandorla: windows from the Everyday to the Sacred, from the Sacred to the Everyday - Morgan, Stephen (Sacred and the Everyday: Comparative Approaches to Literature, Religious and Secular, 2021)

Predictive models to the COVID-19 - Bernardo Gois, Francisco Nauber; Lima, Alex; Santos, Khennedy; Oliveira, Ramses; Santiago, Valdir; Melo, Saulo; Costa, Rafael; Oliveira, Marcelo; Henrique, Francisco das Chagas Douglas Marques; Neto, José Xavier; Martins Rodrigues Sobrinho, Carlos Roberto; Lôbo Marques, João Alexandre (Data Science for COVID-19, 2021)
Following the World Health Organization proclaims a pandemic due to a disease that originated in China and advances rapidly across the globe, studies to predict the behavior of epidemics have become increasingly popular, mainly related to COVID-19. The critical point of these studies is to discuss the disease's behavior and the progression of the virus's natural course. However, the prediction of the actual number of infected people has proved to be a difficult task, due to a wide range of factors, such as mass testing, social isolation, underreporting of cases, among others. Therefore, the objective of this work is to understand the behavior of COVID-19 in the state of Ceará to forecast the total number of infected people and to aid in government decisions to control the outbreak of the virus and minimize social impacts and economics caused by the pandemic. So, to understand the behavior of COVID-19, this work discusses some forecast techniques using machine learning, logistic regression, filters, and epidemiologic models. Also, this work brings a new approach to the problem, bringing together data from Ceará with those from China, generating a hybrid dataset, and providing promising results. Finally, this work still compares the different approaches and techniques presented, opening opportunities for future discussions on the topic. The study obtains predictions with R2 score of 0.99 to short-term predictions and 0.93 to long-term predictions.
Keywords: COVID-19; Forecast; Holt Winters; Kalman filter; Machine learning; Prophet; SEIR

Religious Epistemology in Analytic Theology - McNabb, Tyler Dalton; Baldwin, Erik (T&T Clark Handbook of Analytic Theology, 2021)

Ritual and the Sacred in Peter Shaffer's Theatre - Phillips, Jenny O. L. (Sacred and the Everyday: Comparative approaches to literature, religious and secular, 2021)

Soka Education Philosophy as a Foundation for Teacher Preparation in Creating Inclusive Education - Agbenyega, Joseph Seyram; Ikegami, Kiiko; Rivalland, Corine (International Perspectives on Inclusive Education, 2021)
Current global shifts in education towards inclusive early childhood education are deeply engineered by the crisis of educational exclusion. In responding to exclusion, teachers have mainly utilized dominant western theories to plan and implement inclusive teaching. In this chapter, we draw on a non-western philosophy, a Nichiren Buddhist (Soka) philosophy, to provide a ‘kaleidoscopic’ lens through which to create inclusive educational learning spaces that engender full participation of all children. The Soka education philosophy is a humanist concept which can guide teachers when preparing to create inclusive education. The aims of this chapter are threefold: The first is an exploration of the Nichiren Buddhist (Soka) philosophy. The second aim is to highlight how this philosophy can enable teachers to unleash the unlimited potential of children in inclusive learning settings. Thirdly, we argue that grounding early childhood teacher education in this philosophy can help improve the effectiveness of inclusive educational experience for all children.

The Metaxological Philosophy of Dialogue with Buddhism - Duraj, Jaroslaw (The Wheel & The Cross: An Anthology by Jesuits & Friends on Buddhism and Dialogue, 2021)

Time, authenticity and photographic storytelling in The Museum of Innocence. - Hannam, Kevin; Ryan, Edward (Authenticity and authentication of heritage, 2021)

Towards an Approach to the Interactive Filmic Narrative - Caires, Carlos Sena (Image in the post-millennium: mediation, process and critical tension, 2021)

Translating Two Minds in the Tradition of One Faith: Considerations of Intercultural Dynamics in the parallels of John Henry Newman (1801-1890) and Joseph Ma Xiangbo (1840-1939) - Law, Cyril Jerome (Sacred and the Everyday: Comparative Approaches to Literature, Religious and Secular, 2021)
Interculturality is considered a constant given in the development of most major religious movements during the process of propagation coming into contact with diverse tongues, mores, and sentiments. And one of the chief, if not decisive, instruments contributing to this ever dynamic spread and reception of beliefs and cultures is translation. Christianity purports to be an incarnational religion, where the Word made flesh expresses the di-vine in human terms. Its doctrines are enshrined in a faith tradition that is developed largely through interpretation and translation. This short paper will cut into this sacral literary tradition by paralleling two influential mod-ern Christian thinkers, John Henry Newman from the Anglophone school, and Joseph Ma Xiangbo from the Orient, to see how attempts at translating the ideas and works of people from distinct cultural milieux is both reflec-tive of the necessary developmental nature of Christian teachings in the historical continuum of time and space, and indicative of the intellectual challenges that never cease to accompany the literary effervescence stem-ming from comparative religious studies.

Virtual Guia Fortress: A 3D-printed eXtended Reality Playset - Chau, Iok Fong; Cardoso, Jorge C. S.; Estadieu, Gerald (Entertainment Computing – ICEC 2021, 2021)

What Goes Around Comes Around? The (Non-)Existence of (Divine) Retribution in Ancient Chinese Literature and the Hebrew Bible - Leong, Andrew Chin Hei (Sacred and the Everyday: Comparative Approaches to Literature, Religious and Secular, 2021)

Zen-Ignatian Training Program in Japan: A Personal Experience - Duraj, Jaroslaw (The Wheel & The Cross: An Anthology by Jesuits & Friends on Buddhism and Dialogue, 2021)